2019
DOI: 10.1111/aje.12601
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Prosopis juliflora invasion in the Lake Baringo basin and environmental correlations

Abstract: The spread of Prosopis juliflora in the Baringo basin, Kenya, has led to severe changes in the ecosystem with negative socio‐economic impacts. The drivers that foster the invasiveness of Prosopis are not fully understood. Thus, a method to quantify the degree of infestation will support the determination of environmental preferences and the risk assessment of future Prosopis invasion. We developed a methodology for characterising and classifying degrees of Prosopis infestation in vegetation stands and propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Ongoing projects are dealing with distribution models of invasive species in Eastern Africa, in particular on Prosopis juliflora (Sw.) DC. (Alvarez et al 2019) and Parthenium hysterophorus L. (no publications to date).…”
Section: Resulting Publicationsmentioning
confidence: 99%
“…Ongoing projects are dealing with distribution models of invasive species in Eastern Africa, in particular on Prosopis juliflora (Sw.) DC. (Alvarez et al 2019) and Parthenium hysterophorus L. (no publications to date).…”
Section: Resulting Publicationsmentioning
confidence: 99%
“…Several studies have suggested that P. juliflora has allelopathic effects on other plant species. For instance, Alvarez et al (2019) pointed out that the leaves of P. juliflora contain various chemicals including, tannins, flavonoids, steroids, hydrocarbons, alkanoids, and waxes. These chemicals are known to have effects on the germination of other plant species.…”
Section: Allelopathic Effects Of Prosopis Julifloramentioning
confidence: 99%
“…Different invasive processes can be differentiated by their specific background (for further information, see Vehrs forthcoming). Prosopis juliflora has spread around Lake Baringo (Alvarez et al 2019); Opuntia spp. are also present at Lake Baringo and are encroaching on grasslands in the Laikipia highlands (Muniappan et al 2009;Zimmermann et al 2009;Shackleton et al 2017); and Dodonaea viscosa is spreading in the Pokot highlands around Churo (Becker et al 2016).…”
Section: Bush Encroachmentmentioning
confidence: 99%